The physiological correlates of variable gradient cycling performance - Clark, B.; Paton, C.; O'Brien, B. (Journal of Science and Cycling, 2015)
This study investigates the physiological correlates of computer simulated rolling terrain time-trial performance in a group of competitive cyclists. Twenty eight trained cyclists (age 33 ± 10 years, body mass 74.4 ± 7.3 kg, and peak oxygen uptake 64 ± 7 mL/kg.min) participated in this study. Cyclists initially completed a graded exercise test (GXT) to establish measures of peak power output (PPO), peak oxygen uptake ( O2peak), onset blood lactate accumulation (OBLA), ventilatory threshold (VT) and gross efficiency (GE). On a further occasion cyclists then completed a 20-km time-trial over a computer simulated rolling terrain course from which performance time and mean power output were determined. Pearson`s correlation (r) was used to examine the magnitude of the relationship between measures in the GXT and time-trial. There were large to very large (r = 0.51-0.9) correlations between performance time and mean power output in the time-trial and measures of absolute page1image13584O2peak and PPO from the GXT. Correlations between time-trial performance time and physiological measures were further increased when physiological measures were expressed relative to body mass. The smallest correlations (r < 0.3) were reported between time-trial performance time and mean power output when anaerobic threshold parameters were reported as fractional utilisations of peak power. These findings support the use of body mass corrected variables for predicting performance in rolling terrain time-trials. Cyclists preparing for rolling terrain races are recommended to optimise their power to weight ratio to gain a performance advantage.